Strategy for Innovative Development of The National Economy Based on Attracting Foreign Investments - Umarov Fakhriddin Umar ogli (International Journal Of Management And Economics Fundamental, 2025)
This article explores the strategic importance of attracting foreign investments as a key driver for the innovative development of the national economy. In the context of globalization and increasing economic competition, the effective mobilization of foreign capital plays a critical role in enhancing technological progress, improving production efficiency, and promoting sustainable economic growth. The article analyzes the current state of foreign investment inflows, identifies existing barriers, and proposes practical recommendations for creating a more favorable investment climate. Special attention is given to policy reforms, institutional support mechanisms, and the role of innovation ecosystems in fostering long-term economic transformation. The study emphasizes the necessity of aligning investment strategies with national development goals to ensure inclusive and innovation-oriented economic advancement.